Evaluating the Performance of Adaptable Systems Based on AOM: A Case Study Exploring LOM - Oliveira, Fernando Mateus De; Dantas, Ayla; Vilar, Rodrigo De A. (Anais do Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software (SBCARS), 2015)
When we are developing a software system and we know that it will suffer several changes, it is important to make it adaptable, so that changes can be quickly performed with not so much impact. One solution that has been used to develop adaptable systems is the Adaptive Object Model (AOM) Arquitectural Style, through which entities, properties, relationships and behavior are represented as metadata and can be changed by simply changing this metadata stored in a database. However, developing systems with AOM may be complex and its performance is questionable, especially when we want most of the system to be adaptable. One way that has been proposed to quickly develop AOM systems with a lot of reuse is through the LOM (Living Object Model) framework. In this work we show how a system can be developed using this framework and we evaluate the performance overhead of making most of a system adaptable with AOM using LOM. This evaluation is performed through a case study using two versions of a system to manage online exercises, which has been called Educ Service.